Klasifikasi Hasil Seleksi Kompotensi Dasar CPNS Menggunakan Metode Decision Tree - Ravensky T. Silangen; Muhammad Yahya Matdoan (Inferensi, 2022)
Civil Servants (PNS) are one of the jobs that are of interest to various groups of people in Indonesia. The need for qualified and competitive human resources in this era of globalization requires the government to be more serious in recruiting prospective civil servants so that the realization of good service and organizational needs for existing position qualifications can be met. The implementation of the 2021 civil servant candidate selection at Pattimura University is carried out based on the regulations of the State Civil Service Agency with several stages of selection, one of which is the Basic Competence Selection with a predetermined value standard. This study aims to classify the test results of Candidates for Civil Servants at Pattimura University. The data used in this study is secondary data obtained from the State Civil Service Agency in 2021. The method used in this study is the Decision Tree method. The results show that there are 4 classes (classification) with an Accuracy value of 75%, Classification Error of 25%, Kappa of 0.947, Recall of 97.14%, and Precision of 93.94%.